2016
DOI: 10.1093/eurheartj/ehw229
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale community echocardiographic screening reveals a major burden of undiagnosed valvular heart disease in older people: the OxVALVE Population Cohort Study

Abstract: Previously undetected VHD affects 1 in 2 of the elderly population and is more common in lower socioeconomic classes. These unique data demonstrate the contemporary clinical and epidemiological characteristics of VHD in a large population-based cohort of older people and confirm the scale of the emerging epidemic of VHD, with widespread implications for clinicians and healthcare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
322
4
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 484 publications
(348 citation statements)
references
References 37 publications
13
322
4
9
Order By: Relevance
“…We found that low education predicted aortic regurgitation. Education is an established proxy for socioeconomic status that, in turn, is associated with risk of cardiovascular disease, including valvular disease 28, 29. Thus, our data are in line with previous observations.…”
Section: Discussionsupporting
confidence: 92%
“…We found that low education predicted aortic regurgitation. Education is an established proxy for socioeconomic status that, in turn, is associated with risk of cardiovascular disease, including valvular disease 28, 29. Thus, our data are in line with previous observations.…”
Section: Discussionsupporting
confidence: 92%
“…Integration of echocardiography screening strategies with the existing SUS may be a future direction and has been successfully evaluated in different settings. Even in high‐resourced regions, like the United Kingdom, population‐based echocardiographic screening of asymptomatic elderly individuals was feasible, and the presence of valve disease was associated with socioeconomic status 34. In low‐income areas, such as India, a mass screening strategy in rural areas with focused handheld echocardiography performed by nonexperts and remote interpretation, similar to the PROVAR study flow chart, was also successful and revealed an alarming 16% of major echocardiographic abnormalities (32.9% valve disease), with an important contribution of RHD 35…”
Section: Discussionmentioning
confidence: 99%
“…U budućnosti bi prikladna metoda zbrinjavanja A large-scale echocardiographic screening involving 2500 individuals aged > 65 years was conducted to detect undiagnosed VHD (Figure 1). 1 Clinically significant (moderate or severe) undiagnosed VHD was identified in 6.4%. In addition, 4.9% of the cohort had pre-existing VHD (a total prevalence of 11.3%).…”
Section: Aortna Stenozamentioning
confidence: 96%
“…1 Klinički bitna, no još nedijagnosticirana bolest srčanih zalistaka (umjerenoga ili teškoga stupnja) utvrđena je u 6,4 % osoba. U navedenoj kohorti 4,9 % osoba imalo je već poznatu bolest srčanih zalistaka (ukupna prevalencija 11,3 %).…”
Section: Preambleunclassified